Effect of weak Mn doping on optical properties of ZnGeP2 single crystal grown by vertical gradient freezing method - Deng-Hui Yang; Xin-Ling Cao (Materials Research Express, 2020)
ZnGeP _2 single crystals weakly doped by manganese (Mn) were grown by vertical gradient freezing method from polycrystalline batch which was synthesized by the modified two temperature vapor phase transport method. Energy Disperse Spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Fourier Transform Infrared Spectrometry (FTIR) were employed to characterize the doping single crystals. The un-doped and Mn doped single crystals show the same color. XRD results manifest that the obtained Mn doped ZnGeP _2 has tetragonal structure with slight lattice distortion and has no segregation. The EDS results indicate a good stoichiometry of ZnGeP _2 weakly doped with Mn. From the XPS results, the doped single crystal with no impurity phases were successfully obtained by the vertical gradient freezing method. FTIR spectra show a slight decrease in infrared transmittance of Mn doped single crystals.